Combined effect of creatine monohydrate or creatine hydrochloride and caffeine supplementation in runners'performance and body composition - Jeferson Oliveira Santana; Elias de França; Diana Madureira; Bruno Rodrigues; Erico Chagas Caperuto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
Background Creatine monohydrate (CrM) and caffeine are two of the main substances used to enhance athletic performance although some studies say that they impair each other and CrM could promote weight gain. Objective evaluate the association of CrM or creatine hydrochloride (CrHCl) with caffeine (Caf) supplementation on runners' performance and body composition. Methods 16 individuals, both genders (20-30 years) were randomly divided in 3 groups 1) CrM+Caf (n=6), 2) CrHCl+Caf (n=5) and 3) Placebo+Caf (n=5), they did four running sessions per week, during four weeks. Supplementation was given on a double blind manner, CrM+Caf (20g.day-1 per 7 days + 5 g.day-1 per 21 days of CrM), CrHCl+Caf (6g.day-1 per 7 days + 1.5 g.day-1 per 21 days of CrHCl) and Placebo+Caf (20g.day-1 per 7 days + 5 g.day-1 per 21 days of resistance starch). Caffeine ingestion was acutely administered for all groups, 6mg/kg-1 body weight, only in the last day of the experimental protocol. We collected PRE and POST-treatment, body fat (BF), body weight (BW), 10 km time trial (TT), rating of perceived exertion (RPE), delayed onset muscle soreness (DOMS) and gastrointestinal discomfort perception (GDP). Results No differences were found between groups for RPE, DOMS, BF, BW and GDP. TT decreased significantly for CrM+Caf and CrHCl+Caf group, but no for Placebo+Caf. BF decreased significantly in CrHCl+Caf group and lean body mass increased in CrM+Caf and CrHCl+Caf group. Conclusion These data suggest that either CrM or CrHCLsupplementation works synergistically with acute CAF supplementation improving running performance.   RESUMO Efeito da combinação da suplementação de creatina monohidrato ou creatina cloridrato e cafeína na performance e na composição corporal de corredores Creatina monohidratada (CrM) e cafeína são duas substâncias utilizadas para melhorar a performance atlética, embora alguns estudos sugerem que estas substâncias se prejudicam mutuamente, além da CrM promover ganho de peso. avaliar a associação da CrM ou creatina cloridrato (CrHCl) com a cafeína (Caf), na performance e composição corporal de corredores. 16 indivíduos, de ambos os gêneros (20-30 anos) foram divididos em 3 grupos 1) CrM+Caf (n= 6), 2) CrHCl+Caf (n= 5) e 3) Placebo+Caf (n= 5) para realizarem quatro treinos semanais (durante quatro semanas) suplementados com CrM (20g/dia por 7 dias + 5 g/dia por 21 dias) ou CrHCl (6g/dia por 7 dias + 1,5 g/dia por 21 dias) ou amido resistente (Placebo, 20g/dia por 7 dias + 5 g/dia por 21 dias) junto da suplementação aguda de cafeína (6mg/kg de peso corporal), que foi administrada somente no último dia do protocolo. Foram avaliados PRE e PÓS suplementação: gordura corporal (GC), peso corporal (PC), performance 10 km (P10km), percepção subjetiva de esforço (PSE), dor muscular de início tardio (DIT) e percepção de desconforto gastrointestinal (PDG). Não foram encontradas diferenças entre os grupos para PSE, DIT, GC, PC e PDG. O P10km diminuiu significativamente no grupo CrM+Caf e CrHCl+Caf, mas não para o grupo Placebo+Caf. A GC diminuiu significativamente no grupo CrHCl+Caf e a massa corporal magra aumentou no grupo CrM+Caf e CrHCl+Caf. Estes dados sugerem que a suplementação de CrM ou CrHCLfunciona sinergicamente com a suplementação aguda de Cafeína, melhorando a performance na corrida.